Analysis of the Effect of Brand Equity Elements on Brand Loyalty of Teh Pucuk Harum Brand Products and Coca-Cola Brand Mediated by Brand Trust on Generation Z in Solo Raya - Nadilla Setyowati; Moechamad Nasir (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
The primary objective of this research is to investigate how Brand Equity Elements influence Brand Loyalty toward Teh Pucuk Harum and Coca-Cola, with Brand Trust serving as a mediating factor. This study employs a non-probability sampling technique, specifically purposive sampling, which involves the intentional selection of participants based on predefined criteria aligned with the research goals. Data were gathered using a structured questionnaire utilizing a Likert scale to quantitatively assess the variables under study. The target population consists of Generation Z individuals residing in the Solo Raya region who have consumed either Teh Pucuk Harum or Coca-Cola. A total of 211 valid responses were obtained. Findings reveal that components of brand equity namely brand association, brand awarenesss, and perceived quality positively influence brand trust. However, not all variables exert a direct effect on brand loyalty. While brand trust does not directly impact loyalty, it functions as a significant intermediary that fosters consumer commitment. Consequently, cultivating trust in a brand is essential to leveraging brand equity elements effectively in enhancing customer loyalty.